Visitor impact on vegetation and soil along selected trails in Sg. Rawog, Sandakan, Sabah: preliminary assessment and monitoring - Wilter Malandi @ Azwal Aziz; S.R.M. Hashim; R. Hassan (Sabah Forestry Department, 2019)
Preliminary assessment of visitor impact along selected trails in Sg. Rawog has been conducted through species composition, vegetation cover, and soil compaction. The data collected would become a baseline data for future monitoring impact. Study results showed that there was no statistical difference between disturbed and undisturbed plots in terms of vegetation with proximity to the trail, suggesting weak linearity between amount of usage and impact. It indicated the level of trampling impact still under the threshold of diminishing species diversity and it is rather a form of external pressure on vegetation. Besides, the results also showed insignificant difference in terms of soil compaction. However, the results demonstrated that moderate human trampling near camping area over long periods can have devastating impacts on the condition of the soil. A good management plan that emphasizes on the balance between recreational use and environmental protection and taking into consideration the visitor trampling impacts could help in maintaining long-term conservation goals.